Acromegaly management in the Nordic countries : A Delphi consensus survey - Arlien-Søborg, Mai C.; Dal, Jakob; Heck, Ansgar; Stochholm, Kirstine; Husted, Eigil; Feltoft, Claus Larsen; Rasmussen, Åse Krogh; Feldt-Rasmussen, Ulla; Andreassen, Mikkel; Klose, Marianne Christina; Nielsen, Torben Leo; Andersen, Marianne Skovsager; et al. (Wiley-Blackwell, 2025)
Objective: Acromegaly is associated with increased morbidity and mortality if left untreated. The therapeutic options include surgery, medical treatment, and radiotherapy. Several guidelines and recommendations on treatment algorithms and follow-up exist. However, not all recommendations are strictly evidence-based. To evaluate consensus on the treatment and follow-up of patients with acromegaly in the Nordic countries.
Methods: A Delphi process was used to map the landscape of acromegaly management in Denmark, Sweden, Norway, Finland, and Iceland. An expert panel developed 37 statements on the treatment and follow-up of patients with acromegaly. Dedicated endocrinologists (n = 47) from the Nordic countries were invited to rate their extent of agreement with the statements, using a Likert-type scale (1-7). Consensus was defined as ≥80% of panelists rating their agreement as ≥5 or ≤3 on the Likert-type scale.
Results: Consensus was reached in 41% (15/37) of the statements. Panelists agreed that pituitary surgery remains first line treatment. There was general agreement to recommend first-generation somatostatin analog (SSA) treatment after failed surgery and to consider repeat surgery. In addition, there was agreement to recommend combination therapy with first-generation SSA and pegvisomant as second- or third-line treatment. In more than 50% of the statements, consensus was not achieved. Considerable disagreement existed regarding pegvisomant monotherapy, and treatment with pasireotide and dopamine agonists.
Conclusion: This consensus exploration study on the management of patients with acromegaly in the Nordic countries revealed a relatively large degree of disagreement among experts, which mirrors the complexity of the disease and the shortage of evidence-based data.